2020
DOI: 10.1121/10.0002882
|View full text |Cite
|
Sign up to set email alerts
|

How electrically evoked compound action potentials in chronically implanted guinea pigs relate to auditory nerve health and electrode impedance

Abstract: This study examined how multiple measures based on the electrically evoked compound action potential (ECAP) amplitude-growth functions (AGFs) were related to estimates of neural [spiral ganglion neuron (SGN) density and cell size] and electrode impedance measures in 34 specific pathogen free pigmented guinea pigs that were chronically implanted (4.9–15.4 months) with a cochlear implant electrode array. Two interphase gaps (IPGs) were used for the biphasic pulses and the effect of the IPG on each ECAP measure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 44 publications
2
25
0
Order By: Relevance
“…The difference in magnitude and direction of the group difference in IPG effect size was highly dependent on the eCAP parameter and quantification method. Specifically, the group difference changed direction for the linear slope and the maximum eCAP amplitude when changing from the absolute difference (similar trend as Schvartz-Leyzac et al , 2020a ) to the proportional difference (same trend as He et al , 2020a ). The group difference went from being significant to non-significant for the eCAP threshold calculated in a logarithmic scale, the slope calculated using the window method, and the stimulation level offset.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The difference in magnitude and direction of the group difference in IPG effect size was highly dependent on the eCAP parameter and quantification method. Specifically, the group difference changed direction for the linear slope and the maximum eCAP amplitude when changing from the absolute difference (similar trend as Schvartz-Leyzac et al , 2020a ) to the proportional difference (same trend as He et al , 2020a ). The group difference went from being significant to non-significant for the eCAP threshold calculated in a logarithmic scale, the slope calculated using the window method, and the stimulation level offset.…”
Section: Discussionmentioning
confidence: 91%
“…In the absolute difference method, the IPG effect is defined as the difference in eCAP results recorded at different IPGs. This method has been used to quantify the IPG effect on the slope of eCAP I/O function, the maximum eCAP amplitude, and the N1 latency ( Ramekers et al , 2014 ; Schvartz-Leyzac et al , 2020a ), as well as the stimulation level offset ( Prado-Guitierrez et al , 2006 ; Kim et al , 2010 ; Ramekers et al , 2014 ; Skidmore and He, 2021 ). In the proportional difference method, the IPG effect on the eCAP is defined as the proportional change relative to the eCAP result measured at one selected IPG.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the effect of both neurotrophins on the eCAP, separately and a cocktail of both, was assessed using several stimulation protocols, designed to examine different aspects of neural responsiveness to electrical stimulation. eCAPs evoked by single-pulse stimuli have been shown to be informative of the condition of the SGC population ( Prado-Guitierrez et al, 2006 ; Ramekers et al, 2014 , 2015a ; Schvartz-Leyzac et al, 2019 , 2020 ; Vink et al, 2020 ). Although the absolute eCAP measures showed some improvement for the Cocktail group compared to the untreated PBS group (steeper slope of the input-output function, accompanied by a narrower dynamic range), it has been shown that a more accurate prediction of the neural condition can be obtained with relative measures, such as the IPG effect.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to cellular survival, electrophysiological measurements can be used to assess neural health following neurotrophic treatment. Applying electrically evoked compound action potentials (eCAPs), several measures have been reported that reflect neural health, including the inter-phase gap (IPG) effect ( Prado-Guitierrez et al, 2006 ; Ramekers et al, 2014 , 2015b ; Schvartz-Leyzac et al, 2019 , 2020 ; Vink et al, 2020 [all in guinea pig]), recovery measures, and pulse-train responsiveness ( Ramekers et al, 2015a , b ). Treatment with BDNF has shown improved neural responsiveness in addition to an increase in cellular survival in deafened guinea pigs relative to untreated controls ( Ramekers et al, 2015a ; Vink et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For the problem of mechanical arm modeling and control, many researchers have done a lot of research and successfully verified it in experiments or practice. Schwartz-Leyzac and others proposed an online identification method of mechanical arm dynamic model based on RBFNN and achieved good results on 6-DOF industrial mechanical arm [8]. RBF and MLP (multi-layer perceptron) have been successfully used in 6-DOF series mechanical arms, offering a mechanical armic reverse kinematic solution based on a combination of neural networks [9].…”
Section: Related Workmentioning
confidence: 99%